U.S. Corporate Income Tax Reform and its Spillovers - Clausing, Kimberly (IMF Working Papers; Working Paper ;, 2016)
This paper examines the main distortions of the U.S. corporate income tax (CIT), focusing on its international aspects, and proposes a set of reforms to alleviate them. A bold reform to replace the CIT with a corporate-level rent tax could induce efficiency-enhancing reform of the international tax system. Since fundamental reform is politically difficult, this paper also proposes an incremental reform that would reduce tax expenditures, reduce the CIT rate to 25-28 percent, and impose a minimum rent tax on foreign earnings. Finally, this paper analyzes empirically the likely impact of the incremental on corporate revenues outside the U.S.: Though a U.S. rate cut would likely lower revenues elsewhere, implementation of a strong minimum tax could more than offset that effect for most countries with effective tax rates above 15 percent.